The textile materiality as a link between Sustainability and Textile Design in Fashion Education (Revista de Ensino em Artes, Moda e Design, 2024)
The aim of this paper is to discuss how textile materiality can be considered an articulating axis between Sustainability and Textile Design in Fashion Education in Brazil (BR). To this end, a basic, qualitative and descriptive study was carried out, using works selected for convenience and affinity with the research topic. After conducting a narrative review of the bibliography consulted, it was possible to understand the relevance of dealing with sustainable and alternative textile materials in the training of future designers and stylists. To synthesize the theoretical findings, a visual framework was drawn up which can be used in the future by lecturers and students on higher education fashion courses who wish to include socio-environmental guidelines in Textile Design subjects. At the end of the research, it was possible to infer that Sustainability contributes significantly to the advancement of Textile Design and its fixation in Fashion curricula when approached from the perspective of materiality and textile manualities.
Keywords: textile materiality; textile design; sustainability; fashion education